2014
DOI: 10.1128/mcb.00687-14
|View full text |Cite
|
Sign up to set email alerts
|

Novel Functional Complexity of Polycystin-1 by GPS Cleavage In Vivo: Role in Polycystic Kidney Disease

Abstract: dPolycystin-1 (Pc1) cleavage at the G protein-coupled receptor (GPCR) proteolytic site (GPS) is required for normal kidney morphology in humans and mice. We found a complex pattern of endogenous Pc1 forms by GPS cleavage. GPS cleavage generates not only the heterodimeric cleaved full-length Pc1 (Pc1 cFL ) in which the N-terminal fragment (NTF) remains noncovalently associated with the C-terminal fragment (CTF) but also a novel (Pc1) form (Pc1 deN ) in which NTF becomes detached from CTF. Uncleaved Pc1 (Pc1 U )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 65 publications
4
69
0
1
Order By: Relevance
“…Interpretation of these findings must be tempered, however, by the fact that these cells highly overex pressed Pkd1 cDNA from a heterologous promoter and cannot be directly compared with a 3copy BAC transgene in the Pkd2 -/-cells. A recent study has suggested that PC1-NTF can exist stably without PC1-CTF, but PC1-CTF is critically required for PC1-NTF traffick ing (50). In keeping with this, we did not find a profound reduction in PC1-NTF steadystate levels in the absence of PC2.…”
Section: Methodssupporting
confidence: 89%
See 1 more Smart Citation
“…Interpretation of these findings must be tempered, however, by the fact that these cells highly overex pressed Pkd1 cDNA from a heterologous promoter and cannot be directly compared with a 3copy BAC transgene in the Pkd2 -/-cells. A recent study has suggested that PC1-NTF can exist stably without PC1-CTF, but PC1-CTF is critically required for PC1-NTF traffick ing (50). In keeping with this, we did not find a profound reduction in PC1-NTF steadystate levels in the absence of PC2.…”
Section: Methodssupporting
confidence: 89%
“…PC1-CTF showed both endo glycosidase H-resistant (endo H-resistant) and -sensitive forms, whereas the fulllength, uncleaved PC1 protein PC1-FL was entirely endo H sensitive ( Figure 1, B and C, and ref. 50). Endo H resistance defines the fraction of PC1-CTF that traffics past the middle Golgi apparatus to the cell surface.…”
Section: Resultsmentioning
confidence: 99%
“…S5B), the protein product most likely behaves like a C-terminal truncation mutant. These truncation mutants are known to undergo GPS cleavage but fail to mature beyond the ER due to an inability to interact with PC2, which is required for full maturation of PC1 (33,34). This is in marked contrast to the mature, full-length ΔL protein.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the PC1 m1Bei1 protein revealed that it is expressed and undergoes GPS cleavage. However, the resulting cleavage products are sensitive to EndoH, indicating that it is unable to egress from the ER (34). As such, all three of these missense Pkd1 alleles have PKD phenotypes because of decreased levels of mature, cleaved protein.…”
Section: Discussionmentioning
confidence: 99%
“…Many signaling pathways control ADPKD cyst formation such as the mammalian target of rapamycin (mTOR) [56,57], cyclic adenosine monophosphate (cAMP) [58,59], Wnt signaling pathway [44,60], G protein coupled receptor [GPCR] [61] and Signal Transducer and Activator of Transcription (STAT) signaling pathway [62] (Figure 1).…”
Section: Signaling Pathways As Targets In Pkd Treatmentmentioning
confidence: 99%